PENGARUH DAYA TARIK WISATA DAN PROMOSI TERHADAP MINAT BERKUNJUNG WISATAWAN (Desa Wisata Jetis Kecamatan Sambirejo Kabupaten Sragen) - Agus Widoyo; Triyanto Triyanto (Riset Manajemen dan Akuntansi, 2020)
This study examines the interest in visiting tourists by paying attention to tourist attraction and promotion variables so that this research is conducted with the aim of examining the effect of tourist attraction and promotion on tourist interest in visiting. This research is a survey research with the subject of tourists visiting Jetis tourism village, Sambirejo district, Sragen regency with a sample of 40 tourists. The sampling technique used the accidental sampling method. The research instrument was tested for validity and reliability beforehand. The analytical tool used is a multiple linear regression test starting with a series of classical assumption tests to ensure that the regression model with unbiased estimates and testing is reliable. The test results show that partially the tourist attraction variable has a positive and significant effect on the interest in visiting tourists, and promotion has a significant positive effect on the interest in visiting tourists.